2020
DOI: 10.17784/mtprehabjournal.2019.17.679
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the quality of life of elderly people practicing physical activities and competitive sports games.

Abstract: Background: With increasing life expectancy and decreasing fertility rate the aging population is growing significantly, requiring actions that enable melhoraras health and quality of life of older people. Objective: This study aimed compare the perception of quality of life among elderly participants of a traditional exercise program performed in a Basic Health Units (EF-BHU) with practitioners of competitive sports that participate in the Senior Regional Games (JORI). Methods: The study involved 98 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is not difficult to find that sports gamification will have an impact on both of them, and this impact presents a promoting role. In addition, Santos Júnior, et al [26] even revealed the positive role of sports games in improving the physical fitness of the elderly. The reason is that it is closely related to the characteristics of sports games.…”
Section: Discussionmentioning
confidence: 99%
“…It is not difficult to find that sports gamification will have an impact on both of them, and this impact presents a promoting role. In addition, Santos Júnior, et al [26] even revealed the positive role of sports games in improving the physical fitness of the elderly. The reason is that it is closely related to the characteristics of sports games.…”
Section: Discussionmentioning
confidence: 99%